HIV trauma and the emergency departments: The CDC optout approach should be adopted in South Africa - Timothy Hardcastle; Bhakti Hansoti (South African Journal of Bioethics and Law, 2016)
Background. Trauma is the fourth burden of disease in South Africa (SA). The risk group is the same as that for HIV/AIDS. The Centers for Disease Control and the World Health Organization promulgated the opt-out testing system 10 years ago and several high- and lower-middleincome countries have adopted this approach.Objective. To review the feasibility of implementing the opt-out system in SA emergency departments.Methods. We examined the clinical, economic, practical and patient/provider perceptions concerning the scientific and ethical aspects of the opt-out concept.Results. Patients were generally positive about the opt-out system and the overall test rate and disease identification rates were better than with other systems. Although initial costs may increase, the long-term cost benefit and prevention of transmission, due to linking to care,make this option attractive.Conclusion. The opt-out option for patients presenting to emergency departments with an acute life-threatening illness or trauma, and for those in critically ill states in an intensive care unit, is justifiable based on international and regional practices. This also has the potential to advance early highly active antiretroviral therapy and reduce treatment costs and the disease-adjusted life years for HIV management and trauma critical care. SA should adopt an opt-out testing system instead of the current tedious opt-in system.